Strategi Desa Wisata Berbasis Budaya - Siregar, Nurul Aldha Mauliddina; Priyatmoko, Rakhman (Patra Widya: Seri Penerbitan Penelitian Sejarah dan Budaya., 2022)
The cultural perspective in a broad sense covers people’s lives or how the community should be the basis for developing a tourist village. In Petingsari Tourism Village, Sleman Regency, D.I. Yogyakarta, the concept is apllied by the manager of the tourist village by making the culture or variety of original patterns of community life into a unique and attractive tourist activity for tourists. Village community participation is initiated by implementing empowerment programs. The empowerment strategy is carried out in stages starting with awareness, training, and implementation. As a result, rural communities are able to develop sustainable tourism destinations that have a significant impact on community welfare, nature conservation, and do not interfere with local cultural values due to tourism activities. The purpose of the study was to analyze the processes and strategies implemented by the village government of Pentingsari in initiating the presence of a cultural-based tourism village. The descriptive approach is a research method carried out with data collection techniques through interviews, observations, direct observations, as well as literature studies and visual documentation.